2021
DOI: 10.1021/acs.jpcb.1c00142
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Nanoparticles with Cyclic-Polymer-Grafted Shells Are More Stable than with Linear-Polymer-Grafted Shells: Effect of Polymer Topology, Molecular Weight, and Core Size

Abstract: Polymer brush-grafted superparamagnetic iron oxide nanoparticles can change their aggregation state in response to temperature and are potential smart materials for many applications. Recently, the shell morphology imposed by grafting to a nanoparticle core was shown to strongly influence the thermoresponsiveness through a coupling of intrashell solubility transitions and nanoparticle aggregation. We investigate how a change from linear to cyclic polymer topology affects the thermoresponsiveness of poly(2-isop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…Except for the hightemperature regime, both the brush-brush overlap and the attraction strength are weaker for the ring brushes compared to their equivalent linear counterparts. This DFT result is in agreement with recent experiments, [29] dissipative particle dynamics simulations, [39] and lattice-based SCF theory. [41]…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Except for the hightemperature regime, both the brush-brush overlap and the attraction strength are weaker for the ring brushes compared to their equivalent linear counterparts. This DFT result is in agreement with recent experiments, [29] dissipative particle dynamics simulations, [39] and lattice-based SCF theory. [41]…”
Section: Resultssupporting
confidence: 92%
“…Having confirmed that the trends in DFT density profiles of linear and ring brushes agree with the earlier simulation [33,39] and mean-field studies, [41] we next focus on two opposing parallel brushes, their overlap, and their interaction, which are the keys for analyzing colloidal steric stabilization. [1,29] To this end, Figure 1b shows representative DFT results for total monomer density profiles 𝜌 1 (z) and 𝜌 2 (z) of two opposing linear (upper panel) and ring (lower panel) brushes at T = 2 at their respective equilibrium separations. For the linear brush, we set N = 32 and 𝜎 g = 0.06, while an "equivalent" ring brush is obtained 3b below).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations